2018
DOI: 10.1038/s41423-018-0013-3
|View full text |Cite
|
Sign up to set email alerts
|

T cells from induced and spontaneous models of SLE recognize a common T cell epitope on β2-glycoprotein I

Abstract: Systemic lupus erythematosus is a prototypic model for B-cell epitope spread in autoimmunity. Autoantibodies to numerous molecularly distinct self-antigens emerge in a sequential manner over several years, leading to disease manifestations. Among the earliest autoantibodies to appear are those targeting phospholipid-binding proteins, particularly β2-glycoprotein I. Notably, mice immunized with β2-glycoprotein I and lipopolysaccharide develop a strong T cell response to β2-glycoprotein I that is associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…This loss of tolerance subsequently leads to uncontrolled T cell overactivation and the overproduction of autoantibodies against multiple self-antigens that trigger inflammation and damage to tissues including the skin, joints, vessels, kidneys, and central nervous system. [1][2][3][4] Recent studies have shown that multiple epigenetic regulatory mechanisms contribute to the pathogenesis of SLE. [5][6][7][8] MicroRNAs (miRNAs) regulate target gene expression by binding to the 3′-untranslated region (3′-UTR) of target messenger RNAs (mRNAs), leading to either translational repression or degradation.…”
Section: Introductionmentioning
confidence: 99%
“…This loss of tolerance subsequently leads to uncontrolled T cell overactivation and the overproduction of autoantibodies against multiple self-antigens that trigger inflammation and damage to tissues including the skin, joints, vessels, kidneys, and central nervous system. [1][2][3][4] Recent studies have shown that multiple epigenetic regulatory mechanisms contribute to the pathogenesis of SLE. [5][6][7][8] MicroRNAs (miRNAs) regulate target gene expression by binding to the 3′-untranslated region (3′-UTR) of target messenger RNAs (mRNAs), leading to either translational repression or degradation.…”
Section: Introductionmentioning
confidence: 99%
“…T‐cell responses are shown for LPS‐stimulated BMDCs, as responses with unstimulated BMDCs were very low (data not shown). Only CD4 T cell responses were evaluated, as we have previously shown that mainly CD4, and not CD8, T cells are expanded in β 2 GPI/LPS‐immunized mice . While apoptotic cells suppressed the T‐cell response to β 2 GPI, as measured by interferon‐γ (IFN‐γ) production, necroptotic cells increased the response in a dose‐dependent manner (for dead cell: BMDC ratios of 0.0625, 0.25 and 1) (Figure , bottom).…”
Section: Resultsmentioning
confidence: 99%
“…Only CD4 T cell responses were evaluated, as we have previously shown that mainly CD4, and not CD8, T cells are expanded in b 2 GPI/LPSimmunized mice. 33 While apoptotic cells suppressed the Tcell response to b 2 GPI, as measured by interferon-c (IFN-c) production, necroptotic cells increased the response in a dose-dependent manner (for dead cell: BMDC ratios of 0.0625, 0.25 and 1) (Figure 3, bottom). Similar findings were observed for IL-2 production by T cells treated with apoptotic cells or necroptotic cells (Figure 3, bottom).…”
Section: Necroptotic Cells Promote Antigen Presentation Of B 2 Gpi Tomentioning
confidence: 99%
“…Considering the role of necroptosis in the pathogenesis and development of SLE [13][14][15][16], we aimed to analyze MLKL mRNA of PBMCs and figure out whether it could serve as a biomarker for disease diagnosis and monitoring.…”
Section: Introductionmentioning
confidence: 99%